The Four Paradoxes That Stop Practitioners from Using Research to Change Professional Practice and How to Overcome Them - Riikka Hofmann (MDPI AG, 2024)
This study addresses the puzzle that despite significant policy efforts, research-use in practice remains rare in education even when practitioners are keen. Healthcare has encountered similar problems, and we know little about the nature of the challenges that stop practitioners from developing new research-informed practices. The literature on cross-sector research utilisation, professional learning and practice change all highlight the role of practitioner agency, collaboration and sociocultural norms in research-use, but we lack theoretical insights into how these play out in practitioners' research-use. Moreover, the risks involved are rarely addressed. This study contributes to developing intermediate theory about the mechanisms influencing practitioners' success at using research to develop new practices in education and healthcare. It develops a novel methodological approach, utilising the dialogic difference-within-similarity method, to enable the analysis and synthesis of findings from five close-to-practice studies of research-use in education and healthcare settings in order to generate conceptual insights into the mechanisms at play when practitioners use research to change practice. It finds that four key mechanisms function in a paradoxical manner to hinder research-use, theorising these as the paradoxes of agency, people, norms and risk. I conclude by proposing a conceptual model for overcoming these paradoxes to facilitate research-use at scale.